Masyarakat Multikultural: Konsepsi, Ciri dan Faktor Pembentuknya - Nurhayati, Ifa; Agustina, Lina (Universitas Islam Lamongan, 2020)
Indonesia is widely known as a plural society in addition to popularly being a multicultural nation. Not only does it have the wealth of natural resources, but also it has the most vibrant socio-cultural wealth in the world. This cultural diversity becomes an inevitable reality. Thus looking at the concept of multicultural society, it is as relevant as an epistemic basis that Indonesian people could live together, but at the same time have the potential for possible